ExTENDS: Efficient Data Placement and Management for Next Generation PCM-Based Storage Systems - Mativenga, Ronnie; Hamandawana, Prince; Kwon, Se Jin; Chung, Tae Sun (IEEE Access, 2019)
Although flash memory solid state drives (FSSDs) outperform traditional hard disk drives (HDDs), their performance still fails to cope up with the perennial doubling speeds of microprocessors, regardless of the available high bandwidth. To alleviate this bottleneck, many semiconductor companies, such as Intel, Micron, Samsung, and Hynix have already recently manufactured faster and more scalable non-volatile memory (NVM) technology as main memory but none so far have publicly announced their implementation or production of a full NVM Phase Change Memory SSD (PCM-SSD). Considering implementing NVM-PCM as secondary memory, we can build a future PCM-SSD (PSSD) to replace the slow traditional FSSD. However, a careful design, especially for the controller is essential to hide and manage PCM endurance constraints, in-place-updates ability, bit-Addressability and enabling it to appear as a block device to the host as their predecessors (HDD and FSSD) do. In this paper, we propose implementing ExTENDS, a hardware assumption of NVM-PCM instead of the NVM-flash memory as our future secondary/persistent memory in storage systems. We further present a PCM file translation layer (PhaseFTL) that can efficiently manage address translations from a host file system to PCM while hiding PCM constrains and allowing the PCM blocks to wear down evenly. Moreover, PhaseFTL can efficiently manipulate the bit-Addressability and in-place-update feature of PCM. Our experimental results shows that our proposed PSSD can improve overall SSD performance throughput by an average of 69% compared to traditional FSSDs.
Keywords: Address translation; Hard disk drives; Non-volatile memory; Non-volatile memory technology; Secondary memory; Semiconductor companies; Solid state drives; Translation layers; Cache memory; cache storage; fault tolerance; multipath channels; nonvolatile memory